Measurement of Quality of Lifein Heart Failure-assessment over two Decades - N, Radhika.; P, Anoop.; NVRT, Praveen Kumar; KRT, Sarvana; S, Madhusudhan; GP, Mohanta; PK, Manna (Indian Journal of Pharmacy Practice)
The Quality of Life (QoL), representing a patient-aimed end point in treatment, it has been increasingly emphasized in new heart failure therapies and non – pharmacological therapy. The measurement of QoL depends on the use of validated questionnaire, and with attention paid to the timing of collection of data and also follows up 1 & 2 after patient counselling. Its analysis of data may occur mainly in the context of conventional morbidity and mortality end points. In a review of QoLmeasurement in heart failure published form 1985 to 2005, we found some important data, such as the number of participating subjects in which those patients benefited by the intervention, and some who are not benefited. QoL is analysed as a treatment end point with consideration of the disease with co-morbidity and heart failure disease alone. Improvement in making QoL questionnaire and patient counselling about disease and medications may be helpful to find out the data in the determination of drug efficacy in heart failure.
Keywords: Heart Failure; Quality of Life